PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Felicia Felicia; Arwina Karmudiandri (Jurnal Akuntansi dan Keuangan, 2020)
The aim of this research is to acquire managerial ownership, institutional ownership, audit committee, board of commissioner, independent commissioner, firm size, profitability, and financial leverage in affecting firm value in non-financial companies listed in Indonesia Stock Exchange. In this study, the researcher used 94 listed non-financial companies in Incdonesia Stock Exchange since 2015 until 2017 that have been selected by purposive sampling method. Multiple linear regressions method is used to analysis data. The result of this research indicates that independent commissioner, profitability, and financial leverage have affect to firm value. While managerial ownership, institutional ownership, audit committee, board of commissioner, and firm size did not significantly impact on firm value